The novel and the Arab press - Al-Khuzai, Muhammad Maktouf Naima; Abbas, Hayder Fadhel (Al-Adab Journal, 2021)
This research studies the relationship between journalism and novel in very important period of the modern history. The twenty-first century witnesses a massive information revolution, where journalism and media have more influence in individuals, communities, political & economical systems. etc. This influence includes the literature which reflect the society. A lot of modern research studied the relationship between novel and literary & non- literary types, without focusing on the relationship between novel and journalism according to their history, mutual impact and other interlacement & interlacement. The researcher does not acquaint a study about the deep relationship between journalism & novel, and its most important figure in Arabic novel texts form its early beginning till the present time, which drives the researcher to give this study the title of (Journalism Descriptions in Arabic Novel during 21 Century.Deep historical relationship between novel & journalism, with a lot of journalists who became well known for their both novel & journalism activities, indicate the correlation or even the correlation from the early beginning of novel and journalism. This is in addition to the fact that novel has more free scope where various literary types could be interacting together which makes novel the closest literary type to journalism, since both of them have the narrative element.